2019
DOI: 10.1002/anie.201813356
|View full text |Cite
|
Sign up to set email alerts
|

Dual Photoredox/Copper Catalysis for the Remote C(sp3)−H Functionalization of Alcohols and Alkyl Halides by N‐Alkoxypyridinium Salts

Abstract: Under mild dual photoredox/copper catalysis,t he reaction of N-alkoxypyridinium salts with readily available silyl reagents (TMSN 3 ,TMSCN,TMSNCS) afforded d-azido, d-cyano,a nd d-thiocyanato alcohols in high yields.T he reaction went through ad omino process involving alkoxy radical generation, 1,5-hydrogen atom transfer (1,5-HAT) and copper-catalyzed functionalization of the resulting C-centered radical. Conditions for catalytic enantioselective d-C(sp 3 )ÀH cyanation were also documented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
82
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 166 publications
(89 citation statements)
references
References 70 publications
1
82
0
3
Order By: Relevance
“…In this catalytic cycle, copper went through three oxidation states and the high-valent Cu(III) species, difficult to access by classic oxidative addition, would be formed via a SET process. Although most of radical-Cu(II) rebound processes involved activated secondary or tertiary benzylic carbons [42][43][44] , we have very recently shown that it is also possible to functionalize the primary radical in the presence of copper under photocatalysis conditions 45,46 . While dual photocatalyst/Cu catalytic system has emerged as a powerful tool for cross-coupling reactions 47 , the catalytic cycle depicted in Fig.…”
mentioning
confidence: 99%
“…In this catalytic cycle, copper went through three oxidation states and the high-valent Cu(III) species, difficult to access by classic oxidative addition, would be formed via a SET process. Although most of radical-Cu(II) rebound processes involved activated secondary or tertiary benzylic carbons [42][43][44] , we have very recently shown that it is also possible to functionalize the primary radical in the presence of copper under photocatalysis conditions 45,46 . While dual photocatalyst/Cu catalytic system has emerged as a powerful tool for cross-coupling reactions 47 , the catalytic cycle depicted in Fig.…”
mentioning
confidence: 99%
“…Zhu und Bao haben vor kurzem die Kombination ähnlicher 1,5‐HAT‐Prozesse mit kupferkatalysierten Kreuzkupplungen erzielt (Schema ) . Dieses duale Katalysatorsystem ermöglichte die Einführung von Azido‐, Cyan‐ und Thiocyanatgruppen an distalen C‐H‐Gruppen aus leicht verfügbaren N ‐Alkoxypyridiniumsalzen 37 .…”
Section: Pyridiniumsalze Als Reagenzien Zur üBertragung Funktionellerunclassified
“…During the course of the reaction, direct defluorination to sulfonamide or 1,2-elimination of HF to imine under base conditions was often observed, which might explain the low yields. Examination of the solvent effect showed that CHCl 3 was the best, with a substantial increase of yield to 78%; other solvents, including CH 2 Cl 2 , CH 3 CN, 1,4dioxane and PhCl, only gave inferior results (entries [10][11][12][13][14]. Further changing the reaction temperature to 90°C, 30°C or room temperature gave only unsatisfactory yields (entries [15][16][17], demonstrating the vital thermal effect.…”
Section: Communicationsmentioning
confidence: 99%
“…[11] Moreover, site-selective thiocyanation of C(sp 3 )À H bonds would represent a very attractive and efficient method for preparing alkyl thiocyanates. However, although several interesting studies have recently been published on the thiocyanation of C(sp 3 )À H bonds, these are often limited to the benzyl position, [12] and only two examples have been reported for alkyl C(sp 3 )À H thiocyanation [13] (Scheme 1). Clearly, efficient siteselective alkyl C(sp 3 )À H thiocyanation with general substrate scope remains worthy of investigation.…”
mentioning
confidence: 99%